2014
DOI: 10.14348/molcells.2014.0081
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference-Mediated Knockdown of Astrocyte Elevated Gene-1 Inhibits Growth, Induces Apoptosis, and Increases the Chemosensitivity to 5-Fluorouracil in Renal Cancer Caki-1 Cells

Abstract: Astrocyte elevated gene-1 (AEG-1) is a recently discovered oncogene that has been reported to be highly expressed in various types of malignant tumors, including renal cell carcinoma. However, the precise role of AEG-1 in renal cancer cell proliferation and apoptosis has not been clarified. In this study, we transfected the renal cancer cell line Caki-1 with a plasmid expressing AEG-1 short hairpin RNA (shRNA) and obtained cell colonies with stable knockdown of AEG-1. We found that AEG-1 down-regulation inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
(39 reference statements)
2
18
1
Order By: Relevance
“…Consistent with our results, previous studies showed that ectopic expression of AEG‐1 enhanced the proliferation and anchorage‐independent growth of cancer cells . Similar results have been found in breast cancer, cervical carcinoma, colon cancer, and renal cancer . In addition, AEG‐1 also increases the expression of multidrug resistance gene 1 and contributes to tumour chemoresistance …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Consistent with our results, previous studies showed that ectopic expression of AEG‐1 enhanced the proliferation and anchorage‐independent growth of cancer cells . Similar results have been found in breast cancer, cervical carcinoma, colon cancer, and renal cancer . In addition, AEG‐1 also increases the expression of multidrug resistance gene 1 and contributes to tumour chemoresistance …”
Section: Discussionsupporting
confidence: 81%
“…Ectopic expression of AEG-1 inhibits the apoptosis induced by serum starvation in primary human fetal astrocytes, 31 and AEG-1 silencing promotes apoptosis in renal cancer cells. 27 In the present study, apoptosis in melanoma cells was enhanced by AEG-1 silencing, which was further evidenced by increased chromatin condensation and increased cleaved caspase-3 levels. Both Bax and Bcl-2 proteins closely related to apoptosis.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…20 The mRNA expression levels of OXGR1, AKT1, PIK3CG, PCNA, CDK1, CyclinD1 and FOXO3 were detected by quantitative real-time polymerase chain reaction (qPCR). 20 The mRNA expression levels of OXGR1, AKT1, PIK3CG, PCNA, CDK1, CyclinD1 and FOXO3 were detected by quantitative real-time polymerase chain reaction (qPCR).…”
Section: Quantitative Real-time Polymerase Chain Reaction Assaysmentioning
confidence: 99%